TANTANGAN KOMPETENSI HAKIM DALAM MENANGANI DEEPFAKE - Muhammad Ilham Ramadlan; Khoiron Maulana; Muhammad Zahrudin Afnan (JOURNAL SAINS STUDENT RESEARCH, 2025)
The misuse of Deepfake is one of the types of cybercrime. Judges, as one of the pillars of the Indonesian legal system, are required to always hold their competence in adjudicating this case. Through this research, the author tries to examine regulations related to the competence of judges, the challenges they face in handling Deepfake, and solutions to these challenges. This research is a normative juridical research with a legislative approach. The data collection method of this research uses library research method, and the analysis method uses descriptive qualitative analysis method.